Current anti-inflammatory strategies for treatment of heart failure: From innate to adaptive immunity - Erin B. Taylor; John E. Hall; Alan J. Mouton (Pharmacological Research)
Cardiovascular disease (CVD) is the leading cause of death in developed countries worldwide, often manifesting in the form of heart failure (HF). Recent successful clinical outcomes of anti-inflammatory therapies in HF patients have greatly boosted interest in basic and translational research on the role of inflammation in development of HF. In this review, we discuss recent and ongoing therapies targeting inflammation in CVD/HF, including broad-spectrum anti-inflammatory drugs, supplements, and biologicals such as canakinumab and anakinra. We also discuss the growing body of literature supporting off-target/anti-inflammatory actions of mainline CVD/HF agents, including guideline-directed medical therapy (GDMT) drugs that target the neurohormonal axis, and statins. We discuss therapeutics that target autoimmune mechanisms, and their implications for treating patients with autoimmune diseases with HF or at-risk of developing HF. We also discuss recent evidence for vaccines in modulating the immune response during HF. We conclude that despite the wealth of knowledge gained in the past decade, the therapeutic efficacy of anti-inflammatory therapy is driven by many biological and logistical factors that vary from patient to patient. Furthermore, more studies are needed to understand the adaptive/autoimmune component of HF, particularly in women and patients with pre-existing autoimmune disease. As the number of patients with HF patients who suffer from obesity, diabetes, or autoimmune disease continues to grow, our understanding of inflammation must continue to evolve to reflect these underlying co-morbidities.